Association between self-reported oral health and cognitive function among the community-dwelling elderly in Jinan, China: the mediating effect of life satisfaction - Liu, Guangwen; Lu, Zhongqian; Shan, Ying; Wang, Jieru; Shi, Xinfei; Zong, Di; Li, Shixue; Kong, Fanlei (Frontiers in Psychology, 2023)
Background Deterioration of self-reported oral health and decline in cognitive function are two main adverse health outcomes experienced by the older adults. Little evidence was found on the psychosocial mechanism between self-reported oral health and cognitive function. This study explores the association between self-reported oral health and cognitive function and examines the mediating effect of life satisfaction among the community-dwelling elderly in Jinan, China. Methods A total of 512 older individuals (60+) were included in the study. Cognitive function was assessed using the Chinese version of the Mini-Mental State Examination scale (MMSE), and self-reported oral health was measured using the Chinese version of the Geriatric Oral Health Assessment Index (GOHAI). Pearson correlation analysis was used to determine the relationship between self-reported oral health, life satisfaction, and cognitive function. Multivariate linear regression analysis was conducted to explore the possible effect of covariates. Structural equation modelling and Bootstrap analyses were conducted to verify the mediating role of life satisfaction. Results The mean MMSE score was 25.65 ± 4.42. Better self-reported oral health was significantly associated with a higher level of life satisfaction, and those with higher life satisfaction experienced better cognitive function. Age, educational level and source of living expenses were found to be cofounding variables. Life satisfaction partially mediated the effect of self-reported oral health on cognitive function (95% confidence interval [CI]: 0.010 to 0.075). The mediating effect of life satisfaction accounted for 24% of the total effect. Conclusion The level of cognitive function was relatively high. Self-reported oral health was positively associated with cognitive function, and the mediating effect of life satisfaction was proven to exist in the community-dwelling older individuals. Early screening for oral diseases and a greater focus on life satisfaction are recommended.